3D asymmetry of operated children with oral clefts. (15th July 2013) - Bugaighis, I.; Mattick, C. R.; Tiddeman, B.; Hobson, R.
Structured Abstract Objectives To explore three‐dimensional (3D) facial asymmetry differences in operated children with oral clefts and to compare the results with a control group. Setting and Sample Population The sample comprised one hundred and three 8‐ to 12‐year‐old children: 40 with unilateral cleft lip and palate (UCLP); 23 with unilateral cleft lip and alveolus (UCLA); 19 with bilateral cleft lip and palate (BCLP); 21 with cleft palate (CP) and 80 sex‐ and age‐matched controls living in the North East of England. Materials and Methods 3D stereophotogrammetric facial scans were recorded for each participant at rest. Thirty‐nine landmarks were recorded for each scan. The x, y and z coordinates for each landmark were extracted. Kruskal–Wallis and Mann–Whitney tests were conducted to identify 3D landmark asymmetry differences between the groups. Results Statistically significant differences were observed between all the groups. The UCLP and UCLA patients displayed the greatest asymmetry, followed by the BCLP group. The CP group was the least asymmetric among the cleft groups. Asymmetry was present to a lesser extent in the control group. Conclusions Shape analysis indicates the possible differences in the aetiology and growth pattern of the CP group compared to UCLA or UCLP and BCLP groups.